The Use of Code-Switching and Code-Mixing in English Learning for Children: : A Study Case of Indonesian-American Couple - Sihombing, Lambok Hermanto; Rani, Susvita Dwi (Lingua Cultura, 2022)
The research aimed to determine the types of communication applied in an intercultural family. They had diverse nationalities, customs, values, and beliefs. The researchers viewed communication as the main issue that could occur in an intercultural family. One of the examples of an intercultural family was Aprillia, a Makassarese woman married to Shawn Mullins, a U.S Military. They caused code-switching and code-mixing, types of code-switching and code-mixing applied in the family, children’s communication process, and strategies to solve communication problems in the intercultural family. The research’s finding was gathered from April’s family using an in-depth interview. By applying a qualitative approach, the researchers found the type of code-switching, code-mixing, and communication processes applied in April’s family. Furthermore, the researchers discover that techniques for resolving communication problems and linguistic barriers include avoiding ethnocentrism, challenging prejudices, recognizing differences, adjusting communication, equality, and a balanced split. Consequently, the most effective technique for resolving communication issues within an intercultural family is to remember that every individual has a distinct perspective. To avoid miscommunication during a conversation, individuals must learn to adapt to the capacity of the person with whom they are communicating.